Junções e anéis tipo Y de nanotubos de carbono - Grimm, Daniel (2003)
Carbon nanotubes are cylindrical molecules which present interesting mechanical and electronical properties and may be described as a single graphene sheet rolled up as a tube. Depending only on their geometrical details, these systems may exhibit metallic or semiconducting behaviour and are excellent candidates as uasionedimensional conductors. Based on recent experimental evidences of the large-scale synthesis and production of junctions of type Y, X and T, made of carbon nanotubes, we analyze the electronic properties of a family of Y-shaped junctions [Y-junction]. We address here also the possibility of joining two Y-junctions forming ring-like structures that come naturally connected to a pair of carbon-nanotube leads. First we study if such idealized carbon-molecular structures are structurally stable under variation of temperature, performing numerical Monte Carlo simulations using the Tersoff interatomic empirical potential for carbon atoms. Next, we investigate the electrical properties of these structures and show a direct relationship with their geometry and topological defects. Y-shaped structures of multiple terminals and ring-like systems offer new possibilites of manipulating electrical transport and synthetize nanoscopical electronic devices entirely based on carbon nanotubes. We employ a Green functions renormalization formalism entirely defined in real space, using a single band tight-binding Hamiltonian with only one -orbital. We calculate the conductance and local density of states of these systems and compare the results with the strictly one-dimensional counterparts. We show that the length and/or diameter of the legs of the Y-junction and rings play a fundamental role in electronic transport. This way, we explore the possibility of occurrence of destructive and constructive quantum interference which can be manipulated by geometrical parameters of different carbon structures.